Statistical Learning Trajectory Using The Time Context Of Social Media Usage - Intan Permata Sari Nurullah; Fathur Rahmi; Tasnim Rahmat; Haida Fitri (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to design a statistical learning trajectory using social media usage time data as a starting point or learning context. The method used in this study is design research with the stages of preliminary design, design experiment and retrospective analysis. The subjects in this study were several samples of grade XI high school students. The results of this study are a hypothetical learning trajectory design in statistics learning using social media usage time data with a learning trajectory that is the time spent by students in using social media (Tiktok, Instagram and WhatsApp) to find the measure of central tendency, data location and distribution of single data and group data with agreed provisions. Students record the starting point and end point in the activity of recording students' social media usage time and finally students find a statistical formula.